John Kenneth Galbraith and the Seduction of Politics (1908-2006) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
The essay analyses the political biography of John Kenneth Galbraith, a brilliant economist and nonconformist intellectual, who, during his almost century-long life, collaborated with some of the most significant political figures in 20th century US history and co-authored many important pages of United States foreign policy: he worked with Franklin Delano Roosevelt, Adlai Stevenson, John Fitzgerald Kennedy and Lyndon B. Johnson, was the “Price Czar” during the Second World War, interviewed Albert Speer and the nazi leaders after May 1945, served as ambassador to India and became Jawaharlal Nehru’s friend, was a professor at the best American Universities, journalist and reference point of many anti-war and protest movements at the end of the ‘60s. This essay will analyse these and other passages of Galbraith’s prominent political biography, based on the most recent historiographical debate as well as on a variety of primary sources.
Keywords: Galbraith; India; Kennedy; Vietnam; US Foreign Policy